Quality indicators at a surgical center specialized in dermatology - Baldo Amaral, Juliana Aparecida; Spiri, Wilza Carla [UNESP]; De Assis, Márcio Antônio; Carvalho Passos Guimarães, Heloísa Cristina Quatrini; Molina Lima, Silvana Andrea [UNESP] (FapUNIFESP (SciELO), 2020)
Objective: To identify and characterize the most frequent quality indicators used at a public surgical center specialized in dermatology. Methods: Cross-sectional study in which a survey consisting of daily records of the most frequent quality indicators among the 20 existing at the unit was carried out between August 2015 and July 2016. Mean, median minimum ancTmaximum values, standard deviations, and absolute and percentage frequencies were obtained. A p-value lower than 0.05 (p<0.05) was considered as the level of significance. Results: In a total of 595 elective surgeries, outpatient (87.9%), dermatologic (81.3%), and those performed in men (52.6%) with an average age of 54.9 years stood out. The five most frequent indicators were: Cancelled surgeries (17.6%), incomplete nursing records (14%), absenteeism (6.5%), infection in surgical sites in clean surgeries (2.7%), and occupational accidents (2.2%). Conclusions: Identifying and characterizing quality indicators give visibility to local processes and enable decision-making and improvement of the offered services.
INDICADORES DE CALIDAD EN CENTRO QUIRÚRGICO ESPECIALIZADO EN DERMATOLOGÍA
INDICADORES DE QUALIDADE EM CENTRO CIRÚRGICO ESPECIALIZADO EM DERMATOLOGIA
Keywords: Health Care; Perioperative Nursing; Practice Management; Quality Indicators; Quality Management; Surgicenters